The rise of multi-drug resistant Klebsiella pneumoniae in endogenous panophthalmitis: a rare case report - Shaji, Krishna Priya; Sugunan, Megha; Bhaskar, Sheela (International Journal of Research in Medical Sciences, 2025)
Endogenous panophthalmitis is a devastating intraocular infection resulting from hematogenous spread of pathogens, often associated with significant morbidity and mortality. We report a case of fulminant panophthalmitis with orbital cellulitis secondary to carbapenem-resistant Klebsiella pneumoniae (CRKP) bacteraemia in a 71-year-old female with uncontrolled diabetes, chronic kidney disease on haemodialysis, and a recent catheter-related bloodstream infection (CRBSI). The patient presented with severe ocular pain, proptosis, corneal melt, and systemic instability. Imaging revealed vitreous exudates, retinal detachment, and orbital involvement. Blood cultures confirmed CRKP, sensitive only to polymyxin and tigecycline. Aggressive systemic antibiotics and supportive care was initiated, but surgical intervention was deferred due to hemodynamic instability. The patient succumbed shortly due to multiorgan failure. This case underscores the rapid progression of endogenous panophthalmitis in immunocompromised hosts, particularly with multidrug-resistant organisms. Our case highlights the critical need for multidisciplinary management, and prompt source control in catheter-dependent patients. The fatal outcome emphasizes the poor prognosis associated with resistant pathogens, reinforcing the importance of preventive strategies in high-risk populations.